2023
DOI: 10.1039/d3bm00003f
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in hydrogels for preventing tumor recurrence

Abstract: Malignant tumors remain a high-risk disease with high mortality all over the world. Among all the cancer treatments, surgery is the primary approach in clinical treatment of tumors. However, tumor...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 191 publications
0
5
0
Order By: Relevance
“…Moreover, hydrogel wound dressing has good deformability and is helpful for wound repair [ 75 ]. Due to the ability to cover the postoperative site and maintain the continuous release of drugs, hydrogels even have great potential in preventing tumor recurrence [ 76 ]. Through the engineering design of hydrogels, precise control of RNA therapy can be achieved from the hydrogel loading and controlled release of RNA [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hydrogel wound dressing has good deformability and is helpful for wound repair [ 75 ]. Due to the ability to cover the postoperative site and maintain the continuous release of drugs, hydrogels even have great potential in preventing tumor recurrence [ 76 ]. Through the engineering design of hydrogels, precise control of RNA therapy can be achieved from the hydrogel loading and controlled release of RNA [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…[16] Similarly, the FT-IR analysis of PEP-AD revealed that a new peak appeared at 1567 cm −1 , which was attributed to the amine (─NH 2 ) groups of adipic dihydrazide (Figure S2B, Supporting Information). Further, 1 H NMR analysis for PEP-AD showed the characteristic chemical shifts of PEP-AD at 2.7(a), 1.5(b), 1.7(c), and 3.0(d) ppm (Figure S2C, Supporting Information). [17] These results suggested that OPEP and PEP-AD were successfully synthesized.…”
Section: Physicochemical Properties Of Opab Hydrogelmentioning
confidence: 99%
“…[2b,3] Among them, injectable hydrogels provide resolutions for repairing irregular wounds, such as tumor surgeryderived wounds, because they can perfectly fill the rough surfaces of these wounds and can be utilized in minimally invasive surgical treatments. [1,6] However, obstruction of injection tools due to postponed operation or spread of the hydrogel to surrounding tissues of wounds would usually occur. [7] The shearthinning property of an injectable hydrogel may offer solutions to these issues, because it can improve the viscous flow of hydrogel mixture before injection and ensure hydrogel to be injected easily via a syringe.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations